Global Burden of cardiomyopathy and myocarditis in the older adults from 1990 to 2019 - Zhang, Kexin; Cheng, Xuebing; Qu, Na; Song, Hongwei; Luo, Youhong; Ye, Tongtong; Xu, Qian; Tian, Hongzhan; Kan, Chengxia; Hou, Ningning (Frontiers in Public Health, 2022)
Background Cardiomyopathy and myocarditis (CM-MC) are common chronic diseases causing heart failure in older adults. We aimed to analyze the burden of CM-MC in older adults aged 60–89 years at the global, regional, and national levels in 204 countries from 1990 to 2019. Methods Detailed data on CM-MC from 1990 to 2019 were analyzed from the Global Burden of Diseases Study 2019, including incidence, mortality, disability-adjusted life years (DALYs) and the proportion of deaths caused by different risks factors. All results are presented as numbers, age-standardized rates per 100,000 person-years and estimated annual percentage change (EAPC) with an uncertainty interval of 95%. Results Globally, there were 475,458 (339,942–638,363) incidence cases from CM-MC in 2019; with an age-standardized incidence rate (ASIR) of 16 (13–19.3) per 100,000 person-years. And there were 185,308 (154,610–200,448) deaths, with the age-standardized mortality rate (ASMR) being 4.4 (3.7–4.8). CM-MC resulted in 3,372,716 (2,931,247–3,693,622) DALYs, with an age-standardized DALYs rate (ASDR) of 114.8 (98.7–126.1). Estimated annual percentage change (EAPCs) for ARIS, ARMS, and ARDS has decreased. At the national level, the United States of America had the highest mortality [21,372 (18,924–24,241)] and disability-adjusted life years [407,712 (370,234–470,165)]. And China had the highest number of incident cases [122, 266 (85,925–166,095)]. Globally, high systolic blood pressure and alcohol consumption were the top two risk factors for the proportion of CM-MC deaths. Conclusion CM-MC is still an important cause of early death and chronic disability in older adults. Based on this study, public health agencies should seek more effective methods to prevent and treat CM-MC.